Improving Accessibility for Students with Visual Disabilities in the Technology-Rich Classroom. Issue 1 (26th January 2016) - Taylor, Michael A.
ABSTRACT: As higher education has increasingly embraced digital technologies, we have been too slow to acknowledge accessibility issues for students with visual disabilities. One of the earliest promises of information and communication technology was increased accessibility to content. In theory, digitized content should be as equally accessible as the printed word on a screen, a braille keyboard, or an audible voice on a speaker. In the majority of educational technology, this promise has gone unfulfilled, and faculty members are largely unaware of the myriad obstacles that students with visual disabilities confront while navigating the technology-rich classroom. The principles of Universal Design in Instruction (UDI) provide guidance for developing curriculum that maximizes accessibility and usability of course content for all learners, including those with disabilities. This article examines the development of political science courses through the lens of UDI.